Candidate-gene association study searching for genetic factors involved in migraine chronification. (May 2015) - Louter, MA; Fernandez-Morales, J; de Vries, B; Winsvold, B; Anttila, V; Fernandez-Cadenas, I; Vila-Pueyo, M; Sintas, C; van Duijn, CM; Cormand, B; Álvarez-Sabin, J; Montaner, J; et al.
Introduction: Chronic migraine (CM) is at the severe end of the clinical migraine spectrum, but its genetic background is unknown. Our study searched for evidence that genetic factors are involved in the chronification process. Methods: We initially selected 144 single-nucleotide polymorphisms (SNPs) from 48 candidate genes, which we tested for association in two stages: The first stage encompassed 262 CM patients, the second investigated 226 patients with high-frequency migraine (HFM). Subsequently, SNPs with p values < 0.05 were forwarded to the replication stage containing 531 patients with CM or HFM. Results: Eight SNPs were significantly associated with CM and HFM in the two-stage phase. None survived replication in the third stage. Discussion: We present the first comprehensive genetic association study for migraine chronification. There were no significant findings. Future studies may benefit from larger, genome-wide data sets or should use other genetic approaches to identify genetic factors involved in migraine chronification.